The Relationship Between Autistic Symptomatology and Independent Living Skills in Adolescents and Young Adults with Fragile X Syndrome - Hustyi, Kristin M. (J Autism Dev Disord, 2015)
Few studies have examined the relationship between autistic symptomatology and competence in independent living skills in adolescents and young adults with fragile X syndrome (FXS). In this study, 70 individuals with FXS, aged 15 to 25 years, and 35 age- and IQ-matched controls were administered the Independent Living Scales (Loeb, 1996) and the Autism Diagnostic Observation Schedule (Lord et al., 2000). Results showed that higher levels of autistic symptomatology were associated with lower levels of competence in independent living skills in individuals with FXS, but not in controls. These data indicated that the relationship between autistic symptomatology and independent living skills was syndrome-specific. Early intervention strategies that address autistic symptomatology are sorely needed to improve functional outcomes in this population.